2010
DOI: 10.2174/138920310791330659
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Interactions of Oligomeric Alpha-Synuclein: Potential Role in Parkinsons Disease

Abstract: alpha-Synuclein is a small neuronal protein that has been implicated to play an important role in Parkinson's disease. Genetic mutations and multiplications in the alpha-synuclein gene can cause familial forms of the disease. In aggregated fibrillar form, alpha-synuclein is the main component of Lewy bodies, the intraneuronal inclusion bodies characteristic of Parkinson's disease. The loss of functional dopaminergic neurons in Parkinson's disease may be caused by a gain in toxic function of the protein. Elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 156 publications
(200 reference statements)
1
32
0
1
Order By: Relevance
“…Recently, it was demonstrated that the negative impact of aberrantly secreted ASN does not appear to involve internalization of this protein by the recipient neurons [40,41], but it depends on deregulation of various plasma membrane receptors most of which are Ca 2+ channels [28,42,43]. Alternatively, aberrant oligomeric structures of ASN were shown to evoke permeabilization of cellular membranes leading to uncontrolled Ca 2+ influx and synaptic vesicular depletion [27,[44][45][46][47]. In our studies, we generated an oligomeric species of ASN that are able to form annular pore-like structures and observed that treatment of PC12 cells with those oligomers leads to significant increase in cellular Ca 2+ concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that the negative impact of aberrantly secreted ASN does not appear to involve internalization of this protein by the recipient neurons [40,41], but it depends on deregulation of various plasma membrane receptors most of which are Ca 2+ channels [28,42,43]. Alternatively, aberrant oligomeric structures of ASN were shown to evoke permeabilization of cellular membranes leading to uncontrolled Ca 2+ influx and synaptic vesicular depletion [27,[44][45][46][47]. In our studies, we generated an oligomeric species of ASN that are able to form annular pore-like structures and observed that treatment of PC12 cells with those oligomers leads to significant increase in cellular Ca 2+ concentration.…”
Section: Discussionmentioning
confidence: 99%
“…α-Synuclein's cytotoxicity is thought to involve permeabilization of cell membranes [53,54]. This may be preceded by its binding to integrins (cell-surface glycoproteins) because treatment with an anti-integrin antibody, anti-integrin α5β1, partially rescues neuroblastoma cells from cell death after incubation with nitrated α-synuclein [55].…”
Section: Discussionmentioning
confidence: 99%
“…-syn is slightly expanded, lacking a tightly packed secondary structure but more compact than a fully expanded random coil [61]. Amyloid formation of -syn proceeds by a nucleation-dependent mechanism, in which the formation of a partially folded intermediate plays a critical role followed by several morphologically different types of aggregates, oligomers, amorphous aggregates and amyloid like fibrils [58][59][60]62].…”
Section: Parkinson's Disease ( -Synuclein)mentioning
confidence: 99%